Overland Transport Costs : A Review - Coşar, A. Kerem (World Bank, Washington, DC, 2022)
Poor infrastructure and high domestic shipping costs are often cited as important impediments to economic activity in developing countries. Domestic shipping being mostly overland, understanding the level and structure of costs in road freight transportation could thus help formulate policies that aim to lower them. This review provides a summary of overland transport cost estimates with a focus on trucking, the dominant mode of domestic freight. By describing conceptual issues, highlighting sources of data and alternative methodologies with their key findings, it is intended to help practitioners and researchers navigate the literature.